Stachydrine Inhibits PC12 Cell Apoptosis Induced by Aβ25-35 in an in vitro Cell Model of Neurocognitive Disorders - Fu, Huan; Liu, Mei; Yan, Jinxiu; Zhao, Na; Qu, Liangchao (Letters in Drug Design & Discovery, 2021)
Background: Abnormal deposition of amyloid beta (Aβ) is considered the primary cause of neurocognitive disorders (NCDs). Inhibiting cytotoxicity is an important aspect of the treatment of NCDs. Stachydrine (STA) has been widely used for gynecological and cardiovascular disorders. However, whether STA has protective functions in PC12 cells treated with Aβ25-35 remains unclear. Introduction: Traditional Chinese Medicine, stachydrine (STA), is a water-soluble alkaloid of Leonurus heterophyllus, which can inhibit cell apoptosis, suppress tumor growth, maintain homeostasis of myocardial cells, and alleviate endothelial dysfunction. This study will investigate the effect of STA on inhibiting PC12 cell apoptosis induced by Aβ25-35 in an in vitro cell model of neurocognitive disorders. Methods: The differentially expressed genes (DEGs) in cells treated with STA were analyzed according to the Gene Expression Omnibus (GSE) 85871 data, and the STITCH database was used to identify the target genes of STA. PC12 cells were treated with Aβ25-35 and/or STA, 3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was performed and lactate dehydrogenase (LDH) activity was determined. The cell cycle distribution was detected by flow cytometry, and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) or Western blotting were used to detect the expression of genes or proteins. Results: GSE85871 data showed 37 upregulated and 48 downregulated genes among the DEGs affected by STA. The results from the STITCH database showed that RPS8 and EED were target genes of STA. GSE1297 analysis showed the 13 most significantly upregulated genes. STA might affect the occurrence of NCDs through the interaction of TP53 with EED and RPS8. Finally, Aβ25-35 promoted apoptosis and LDH release of PC-12 cells, arrested the cell cycle in the G2/M phase, and inhibited the expression of the RPS8, EED, Bcl-2 and P53 genes. STA could reverse the effect of Aβ25-35. Conclusion: STA may play an important role in inhibiting apoptosis induced by Aβ25-35 by targeting the RPS8 and EED genes in the NCDs model in vitro.
Keywords: traditional chinese medicine